61.3k views
4 votes
Linear Equations

4(t-2) + 2t -4 = 2(9-2t)

1 Answer

5 votes

Hey!


Here is the equation:



4(t-2)+ 2t - 4 = 2(9-2t)


First remove the parentheses and multiply everything. Now it becomes:



4t - 8 + 2t - 4 = 18 - 4t


Combine all the terms with variables(like terms). It becomes:



6t - 12 = 18 - 4t


Add 4t to each side so you can move the variable. It becomes:



10t - 12 = 18


Add 12 to each side to leave the variable alone. It becomes:



10t = 30


At last, divide both sides by 10 to leave the variable by itself.



(10t)/(10) = (30)/(10)


Divide:



\framebox{t = 3}

User Andrepaulo
by
5.0k points